"Puestow modified procedure in the era of advanced endoscopic interventions for the management of chronic lithiasic pancreatitis. A two cases report". (2015) - Fragulidis, Georgios P.; Vezakis, Αntonios; Dellaportas, Dionissios; Sotirova, Ira; Koutoulidis, Vassilis; Kontis, Elliseos; Polydorou, Andreas
Highlights: With the opportunity of two patients with Chronic Lithiasic Pancreatitis (CLP) treated in our hospital where endoscopic procedures failed and were finally surgically managed with modified Puestow procedure, the main considerations in patients with CLP are highlighted. Larger and impacted stones typically require lithotripsy or surgery. In older randomized trials is demonstrated that surgical therapy turns to have more durable results and results in pain relief for longer intervals. The decision for surgical therapy depends on many factors: pancreatic duct diameter, duct strictures, pain severity indexes, malignancy concerns, associated biliary duct obstruction and operative risk. Abstract: Introduction: Pancreatic duct calculi in chronic pancreatitis (CP) patients are the main cause of intractable pain which is their main symptom. Decompression options of for the main pancreatic duct are both surgical and advanced endoscopic procedures. Presentation of cases: A 64-year-old male with known CP due to alcohol consumption and a 36-year-old female with known idiopathic CP and pancreatic duct calculi were managed recently in our hospital where endoscopic procedures were unsuccessful. A surgical therapy was considered and a longitudinal pancreaticojejunostomy (modified Puestow procedure) in both patients was performed with excellent results. Discussion: Over the last 30 years, endoscopic procedures are developed to manage pancreatic duct strictures and calculi of the main pancreatic duct in CP patients. In both of our cases endoscopic therapy was first attempted but failed to extract the pancreatic duct stones, due to their size and speculations. Modified Puestow procedure was performed for both and it was successful for long term pain relief. Conclusion: Despite advancement in endoscopic interventions and less invasive therapies for the management of chronic lithiasic pancreatitis we consider that classic surgical management can be appropriate in certain cases.